Feasibility and Performance of Elastin Trichrome as a Primary Stain in Colorectal Cancer Resection Specimens: Results of an Interobserver Variability Study. (October 2021) - Shivji, Sameer; Kak, Ipshita; Reid, Stephanie L.; Muir, Jennifer; Hafezi-Bakhtiari, Sara; Li-Chang, Hector; Deliallisi, Ardit; Newell, Ken J.; Grin, Andrea; Conner, James; Kirsch, Richard
Abstract : Venous invasion (VI) is a powerful prognostic factor in colorectal cancer (CRC) that is widely underreported. The ability of elastin stains to improve VI detection is now recognized in several international CRC pathology protocols. However, concerns related to the cost and time required to perform and evaluate these stains in addition to routine hematoxylin and eosin (H&E) stains remains a barrier to their wider use. We therefore sought to determine whether an elastin trichrome (ET) stain could be used as a "stand-alone" stain in CRC resections, by comparing the sensitivity, accuracy, and reproducibility of detection of CAP-mandated prognostic factors using ET and H&E stains. Representative H&E- and ET-stained slides from 50 CRC resections, including a representative mix of stages and prognostic factors, were used to generate 2 study sets. Each case was represented by H&E slides in 1 study set and by corresponding ET slides from the same blocks in the other study set. Ten observers (3 academic gastrointestinal [GI] pathologists, 4 community pathologists, 3 fellows) evaluated each study set for CAP-mandated prognostic factors. ET outperformed H&E in the assessment of VI with respect to detection rates (50% vs. 28.6%; P <0.0001), accuracy (82% vs. 59%, P <0.0001), and reproducibility ( k =0.554 vs. 0.394). No significant differences between ET and H&E were observed for other features evaluated. In a poststudy survey, most observers considered the ease and speed of assessment at least equivalent for ET and H&E for most prognostic factors, and felt that ET would be feasible as a stand-alone stain in practice. If validated by others, our findings support the use of ET, rather than H&E, as the primary stain for the evaluation of CRC resections.